2015
DOI: 10.5664/jcsm.4600
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of a Two-Channel Portable Monitor to “Rule in” Obstructive Sleep Apnea

Abstract: Study Objectives:We hypothesized that a dual-channel portable monitor (PM) device could accurately identify patients who have a high pretest probability of obstructive sleep apnea (OSA), and we evaluated factors that may contribute to variability between PM and polysomnography (PSG) results. Methods: Consecutive clinic patients (N = 104) with possible OSA completed a home PM study, a PM study simultaneous with laboratory PSG, and a second home PM study. Uniform data analysis methods were applied to both PM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
1
30
2
2
Order By: Relevance
“…This finding appears to partly contradict the findings of a previous study by Ward and colleagues. 31 Contrary to our results, they found that the AL was less sensitive than the Comp at diagnosing OSA. However, there are several important differences between their study and ours.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding appears to partly contradict the findings of a previous study by Ward and colleagues. 31 Contrary to our results, they found that the AL was less sensitive than the Comp at diagnosing OSA. However, there are several important differences between their study and ours.…”
Section: Discussioncontrasting
confidence: 99%
“…43 Unattended home sleep apnea testing using portable monitors is increasingly available for diagnosing OSA, and has demonstrated good sensitivity and specificity for detecting OSA for patients with a high pretest probability. 44,45 Portable, unattended monitoring may be useful for diagnosing OSA in LTC residents who do not have nighttime confusion or dementia. Those with confusion and dementia are likely to remove the portable monitors resulting in a high percentage of missing data.…”
Section: Factors That Contribute To Sleep Disturbance In Long-term Carementioning
confidence: 99%
“…1 Using a rigorous study protocol of testing the device at home and in the lab (simultaneously with a lab polysomnogram [PSG]) and in a randomized order of testing, they showed that their 2-channel PM (ApneaLink, ResMed, San Diego, CA) was able to reliably confi rm the diagnosis of sleep apnea in those with high pretest likelihood of having OSA (sensitivity 80%, specifi city 83%, positive likelihood ratio 4.8). This study, excepting its limitations, provides much needed validation for the use of a simplifi ed PM to adequately diagnose OSA in a timely fashion in the appropriate patient population.…”
Section: T He Landscape Of Sleep Medicine Is Dramatically Changingmentioning
confidence: 99%
“…Manually scoring the data, rather than relying on the automated scoring algorithm reduced missed cases by up to 18%. 1,4 Similarly, ordering clinicians must be cognizant that PM can underestimate disordered breathing index by as much as 22 events/h. 1 Such results suggest that testing with PM may not only underestimate the severity of disease, but may miss the diagnosis of OSA entirely.…”
Section: T He Landscape Of Sleep Medicine Is Dramatically Changingmentioning
confidence: 99%
See 1 more Smart Citation